Hubungan Pola Makan Ibu Hamil dengan Kelahiran Bayi BBLR di Ruang Cempaka 2 RSUP Prof.Dr.I.G.N.G Ngoerah - Ningrum, Ni Putu Ayu Devy Ratna; Suiraoka, I Putu; Widarti, I.G.A Ari (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2024)
Nutritional deficiencies during pregnancy can inhibit growth and development for the fetus. Malnourished fetuses are at risk of being born with low birth weight. Babies with low birth weight can have an impact in the short and long term. The general purpose of this study was to determine the relationship between the diet of pregnant women and the birth of babies with low birth weight in Cempaka 2 room Prof.Dr.I.G.N.G.Ngoerah Hospital. This type of research is observational which is analytical with a case control study design. The number of samples of this study was 40 people consisting of 20 mothers who gave birth to babies with normal weight and 20 mothers who gave birth to babies with low weight. Data collection with SQ- FFQ questionnaire. The data analysis used was odd ratio and chi square statistical test. The results showed that there was a relationship between maternal diet based on the amount of energy intake (p = 0.011) and the amount of protein intake (p = 0.011) with the incidence of low weight with the results of odd ratio of 5.571 for energy intake and 5.444 for protein intake so that it can be concluded that pregnant women who have less energy and protein intake are 5 times at risk of giving birth to babies with low birth weight and there is no significant relationship between maternal diet based on food type (p = 0.105) with the birth of babies with low birth weight in Cempaka 2 room Prof.Dr.I.G.N.G.Ngoerah Hospital. Nutritionists are expected to educate pregnant women about the importance of a good diet and educate mothers who give birth to babies with low birth weight on the importance of exclusive breastfeeding to babies with low birthweight.